Swallowing Disorder in Multiple Sclerosis: Modified Version of the Screening Tool - Zahra Sadeghi; Mohammadreza Afshar; Abbas Ebadi; Kowsar Baghban; Zahra Sadat Qureshi (University of Social Welfare and Rehabilitation Sciences, 2020)
Objective: Dysphagia is commonly encountered in Multiple Sclerosis (MS). It can consequently cause severe complications such as the increased risk of dehydration, malnutrition and aspiration pneumonia that associated with an increased risk of death in the late stages of the disease. These complications can be prevented with an effective screening protocol. The Dysphagia in Multiple Sclerosis (DYMUS) is the only questionnaire developed specifically for patients with MS. The aim of the present study was translation and cross-culturally adaptation of DYMUS for the Persian population and estimation of the questionnaire's reliability and validity. Also, we investigated the frequency and severity of dysphagia in the patients referring to the Tehran MS Society and its association with the course of MS, disease duration, and Expanded Disability Status Scale (EDSS). Materials & Methods: This is a methodological and descriptive-analytic study. The statistical populations consist of the patients with MS referring to the Tehran Multiple Sclerosis Society in 2018. The study sample consisted of 108 patients who were selected through a convenient sampling method. The research instruments consisted of 10-items DYMUS questionnaire (in the first part of the study, translated and its psychometric properties examined), Dysphagia Handicap Index and a demographic information questionnaire. In methodological section, translation and cross-cultural adaptation were fulfilled and the Confirmatory Factor Analysis (CFA) was used to assess the construct validity and to test the goodness-of-fit of the presented model. The association between the DYMUS and Dysphagia Handicap Index (DHI) scores investigated to convergent validity. ‏ The inter-item correlation matrix was calculated to assess the homogeneity of the questionnaire items. Kuder - Richardson (KR-20) was measured to assess the internal consistency of the questionnaire. Also, the test-retest procedure was conducted on the 19 subjects understudy to assess the reliability. Finally, the frequency and severity of dysphagia and its association with the course of MS, disease duration, and EDSS was investigated. KR-20 reliability coefficient, Intraclass Correlation Coefficient (ICC), inter-item correlation matrix, Mann-Whitney U test and rank correlation coefficient or Spearman's were used to inferential statistical analysis. Results: Analysis of the inter-item correlations matrix indicated a positive correlation between all items, exception item 10. Based on the results of the inter-item correlation, item 10 had the lowest correlation coefficient that was deleted from the questionnaire. CFA results confirmed the two-factor model of DYMUS, "dysphagia for solids" and "dysphagia for liquids", and revealed that the item 10 was minimally contributing to the measurement of "dysphagia of solids" and internal consistency increased after the deletion of this item. Also, the solution of the 9-item Model was the best goodness-of-fit indicator for the sample. The obtained results from the convergent validity indicated a positive significant correlation between the DYMUS and DHI (rs=0.693, P<0.001). A KR-20 reliability coefficient of the DYMUS was 0.856, indicating high internal consistency of the Persian translation of the questionnaire items. Test-retest reliability was excellent with 0.965 value. The results also showed that 65.7% of multiple sclerosis patients had a swallowing disorder. In terms of the dysphagia severity, 25.9% of participants had mild dysphagia, and 39.8% of participants had alarming dysphagia. DYMUS values were significantly correlated with disease duration (rs=0.198, P= 0.040), and EDSS (rs=0.235, P= 0.014) and significantly higher mean scores were observed in the patients with secondary progressive than the other subgroups of multiple sclerosis. Conclusion: The Persian adjusted 9-item questionnaire was demonstrated to be a simple, consistent, valid and reliable tool for the detection of patients who need more specific instrumental evaluations of swallowing. Also, about the dysphagia is very frequent in these patients, it is important that clinicians monitor these patients carefully even in early stages of the disease‏ for early detection and planning a rehabilitation program to the prevention of serious subsequence complications.